(untitled) (Global Journal of Science Frontier Research, 2013)
We have made an attempt to study a pathway fractional integral operator concerning to pathway model and pathway probability density for product of some special functions with a general class of polynomials. Our results are quite general in nature and hence compass a large number of results hitherto in the literature.